Pengaruh Kedisiplinan Belajar terhadap Hasil Belajar Mata Pelajaran Bahasa Indonesia di Kelas III SD Negeri 2 Laompo - Roys Roys (Departement of Mathematics Education, 2024)
The aim of this research is to see the influence of Indonesian language subjects at SDN 2 Laompo. A pre-study or pre-test design is used, i.e. Experimental research applies one test group without a control (comparison) class. The population and research paper are 3rd grade students at SDN 2 Laompo with a total of 20 students. Based on the scores previously explained, it can be seen that the total post-test score (post treatment) of students in class 3 of SDN 2 Laompo is higher than the pre-test score (before treatment). Discipline is something that must be implemented by the entire community, especially students in the school environment. When someone is disciplined in applying discipline, especially in the classroom, the learning process in the classroom will be more comfortable and make students and teachers comfortable in participating in learning. The results of this discipline will be a benchmark for students when they are in the community.